2015
DOI: 10.1111/jnc.13090
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mitochondrial morphology induced by calcium or rotenone in primary astrocytes occur predominantly through ros‐mediated remodeling

Abstract: Morphological changes in mitochondria have been primarily attributed to fission and fusion, while the more pliable transformations of mitochondria (remodeling, rounding, or stretching) have been largely overlooked. In this study, we quantify the contributions of fission and remodeling to changes in mitochondrial morphology induced by the Ca 2+ ionophore 4Br-A23187 and the metabolic toxin rotenone. We also examine the role of reactive oxygen species (ROS) in the regulation of mitochondrial remodeling. In agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 73 publications
4
30
0
3
Order By: Relevance
“…Opposite effects of calcineurin and PKA were also reported as key events in (i) the dynamic fission-fusion events that determine the shape and function of mitochondria [162, 163], thus cell survival; (ii) neuronal output stabilization induced by tonic dopamine via type 1 dopaminergic receptors [164]; and (iii) the phosphorylation/dephosphorylation of serine 897 in the NR1 subunit of the NMDA receptor (pNR1), whose increases in phosphorylation were reported in acute morphine withdrawal [30]. …”
Section: Nervous System Functionmentioning
confidence: 99%
“…Opposite effects of calcineurin and PKA were also reported as key events in (i) the dynamic fission-fusion events that determine the shape and function of mitochondria [162, 163], thus cell survival; (ii) neuronal output stabilization induced by tonic dopamine via type 1 dopaminergic receptors [164]; and (iii) the phosphorylation/dephosphorylation of serine 897 in the NR1 subunit of the NMDA receptor (pNR1), whose increases in phosphorylation were reported in acute morphine withdrawal [30]. …”
Section: Nervous System Functionmentioning
confidence: 99%
“…30 Because atherosclerotic-MSCs display elevated mitochondrial oxidative stress, we next assessed the content (ie, mitochondrial mass), structure, and morphology of their mitochondria. Our results revealed that MSCs from adults with atherosclerosis have increased mitochondrial mass ( Figure 3A) and elongated mitochondria ( Figure 3B), 2 features that may reflect an increase in fusion activity.…”
Section: Mitochondrial Morphology Is Altered In Atherosclerotic-mscsmentioning
confidence: 99%
“…More recent reports have attributed calcium-dependent changes in mitochondrial morphological shape to processes may be independent of Drp1-mediated mitochondrial fission (187, 188). In cortical astrocytes, treatment with a calcium ionophore, 4Br-A23187, increases intracellular calcium levels and leads to a decrease in mitochondrial length (187).…”
Section: Calcium Regulates Mitochondrial Morphology and Intracellumentioning
confidence: 99%
“…However, calcineurin inhibitors attenuate the 4Br-A23187-induced increase in mitochondrial number, suggesting that calcium-mediated changes in mitochondrial morphology can occur independently of a complete fission event. The fission-independent remodeling process is mediated through reactive oxygen species (ROS) as treatment with the antioxidant N-acetylcysteine (NAC) does not increase mitochondrial in combination with 4Br-A23187 treatment but attenuates mitochondrial length shortening (188). Therefore, it is not clear from these findings whether mitochondrial remodeling occurs independently of the canonical fission protein Drp1.…”
Section: Calcium Regulates Mitochondrial Morphology and Intracellumentioning
confidence: 99%